Territory of Student Community Spaces Based on Fixed Elements, Semi-Fixed Elements, and Activity Patterns - Tamimi, Shabrina; Munawarah Panggabean , Siti; Rachma Marcillia , Syam (Institut Seni Indonesia Surakarta, 2024)
Student community spaces are essential facilities provided by universities to support various extracurricular activities. However, these spaces often fail to fully accommodate the diverse needs and activities of students, leading to a process of adaptation where users modify the space by adding both physical and non-physical elements. This study, utilizing behavior mapping and questionnaires, aims to analyze how students use and adapt these community spaces, focusing on the territorial adjustments made through physical elements and user activities. The findings reveal that most space adaptations involve semifixed elements, particularly in areas where informal activities take place. In contrast, formal activities tend to be conducted in indoor spaces where the physical elements are predominantly fixed. These insights highlight the necessity for more flexible and adaptable design strategies in student community spaces to better meet the needs of their users.